Sequestration and efflux largely account for cadmium and copper resistance in the deep‐sea Nitratiruptor sp. SB155‐2 (phylum Campylobacterota). (28th October 2022) - Ares, Ángela; Sakai, Sanae; Sasaki, Toshio; Shimamura, Shigeru; Mitarai, Satoshi; Nunoura, Takuro
Abstract: In deep‐sea hydrothermal vent environments, metal‐enriched fluids and sediments abound, making these habitats ideal to study metal resistance in prokaryotes. In this investigation, we employed transcriptomics and shotgun proteomics with scanning transmission electron microscopy and energy‐dispersive x‐ray spectroscopy (STEM‐EDX) to better understand mechanisms of tolerance for cadmium (Cd) and copper (Cu) at stress‐inducing concentrations in Nitratiruptor sp. SB155‐2 (phylum Campylobacterota). Transcriptomic profiles were remarkably different in the presence of these two metals, displaying 385 (19%) and 629 (31%) differentially transcribed genes (DTG) in the presence of Cd(II) and Cu(II), respectively, while only 7% of differentially transcribed (DT) genes were shared, with genes for non‐specific metal transporters and genes involved in oxidative stress‐response predominating. Transcriptomic and proteomic analyses confirmed that metal‐specific DT pathways under Cu(II) stress, including those involving sulfur, cysteine, and methionine, are likely required for high‐affinity efflux systems, while flagella formation and chemotaxis were over‐represented under Cd(II) stress. Consistent with these differences, STEM‐EDX analysis revealed that polyphosphate‐like granules (pPLG), the formation of CdS particles, and the periplasmic space are crucial for Cd(II) sequestration. Overall, this study provides new insights regarding metal‐specific adaptations of Campylobacterota to deep‐sea hydrothermal vent environments.